(untitled) (Perner’s Contacts, 2011)
People can choose between different ways, how to make their journey. The making-decision is influenced by many factors, which can be for example purpose of their journey, their incomes or ownership of a car. In the paper there is showed travel costs sensitivity on changes in these factors.